Delta efficiency of uphill roller skiing with the double pole and diagonal stride techniques - Hoffman, M. D.; Clifford, P. S.; Watts, P. B.; O'Hagan, K. P.; Mittelstadt, S. W. (Canadian Journal of Applied Physiology, 1995)
Delta efficiencies for uphill roller skiing with the double pole (DP) and diagonal stride (DS) techniques were determined among 4 female and 4 male cross-country ski racers in order to examine for differences between techniques and between the sexes. Each skier roller-skied on a motorized ski-treadmill at 1.7% and 7.1% grades with both techniques at 2 to 4 different speeds. Steady-state oxygen uptake values were used to calculate the differences in metabolic requirements for roller skiing at the 2 grades (delta E). The differences in external work rates between the 2 grades (delta W) were calculated from the work rates for overcoming rolling resistance and elevating the transported mass against gravity. Delta efficiencies (delta W/ delta E) ranged from 14 to 36%, were significantly greater (p < 0.001) for DS than DP, and showed a significant (p < 0.01) velocity effect for DS. Delta efficiencies were 27% greater (p < 0.05) for the women compared with the men for DP, and significant (p < 0.05) correlations were found between efficiency for DP and body mass. This suggests that the higher efficiency with DP for female skiers is at least partially due to their lower body mass.